Low Back Pain Therapy with Back Massage, Acupressure and Ginger Compress - Aura, Jihan; Purwitasari, Neny; Adianti, Myrna (Future Science, 2021)
Low back pain (LBP) is defined as a sensation of pain and discomfort localized below the 12th rib and above inferior gluteal folds. In this case study, based on traditional medicine the client's LBP is due to kidney deficiency syndrome especially the kidney Qi and the damp-cold pathogen attack. Which is caused by bad habits, trauma, the living environment tends to be humid that can injure the kidneys, bladder which makes the kidney Qi weak and cause damp-cold pathogens to settle easily. The purpose is to know the effect of combination therapy for a back massage, acupressure at Shenshu (BL23), Weizhong (BL 40), Taixi (KI 3), and Sanyinjiao (SP 6) and ginger (Zingiber officinale Rosc.) compress on low back pain sufferers. For the methods, the clients with LBP were given massage therapy in the back and acupressure points at Shenshu (BL 23), Weizhong (BL 40), Taixi (KI 3), and Sanyinjiao (SP 6) as well as given ginger herbal compresses (Zingiber officinale Rosc.) 12 times within 1 week 2 times of therapy. The ginger used is red ginger as much as 20 grams each time therapy. The results of the treatment of LBP were that massage combination therapy on the back area and acupressure at the points Shenshu (BL 23), Weizhong (BL 40), Taixi (KI 3), and Sanyinjiao (SP 6) and presented a ginger herbal compress (Zingiber officinale Rosc.) can help with low back pain. Conclusion: Back Massage therapy, acupressure, and ginger compress could reduce low back pain.